A Chemostat Model for Evolution by Persistence: Clade Selection and Its Explanatory Autonomy. Issue 1 (25th January 2023) - Neto, Celso; Doolittle, W. Ford
Abstract: Many contemporary biologists and philosophers of biology admit that selection occurs at any level of the biological hierarchy at which entities showing heritable variation in fitness are found, while insisting that fitness at any level entails differential reproduction, not differential persistence. Those who allow that persistence can be selected doubt that selection on nonreproducing entities can be reiterated, to produce "complex adaptations." We present here a verbal model of subclones evolving in a simple idealized chemostat that calls into question these suppositions and is usefully explanatory when taken as an analogy to selection for persistence of clades.